Capacity Development of Psychology in the Caribbean: Lessons from Far and Near - Amuleru-Marshall, Omowale - (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
This article builds on a presentation of a "Vision for Caribbean Psychological Association/Organization" which was presented in a workshop at the Caribbean Regional Conference of Psychology. It primarily addresses the development and establishment of harmonized systems of legally institutionalizing the profession of psychology across the broader Caribbean. Recognizing the linguistic, cultural, legal and political diversity across the region, proposals are nonetheless made to launch co-existing and complementary arrangements through the emerging regional association of caribbean psychologists. Nurturing relationships with countries and territories that already have existing statutory arrangements by which psychologists are registered or licensed is presented as a way to build and refine appropriate mechanisms in those countries - mainly CARICOM countries - in which the field of psychology is relatively new and derdeveloping. The example of CARICOM nurses is used to illustrate a way forward for psychologists in the Anglophone Caribbean.